Exploring Multidimensional Financial Inclusion and Manufacturing Firms Performance in a Developing Country: The Case of Nigeria - Uchenna Efobi; Belmondo V. Tanankem; Simplice Asongu; Ibukun Beecroft (African Governance and Development Institute (AGDI), 2016)
This study used the matching technique to explore the impact of financial inclusion on the performance of manufacturing firms in Nigeria. Most studies that have considered financial inclusion have largely focused on household access to the services of financial institutions, but have inadvertently underexplored the impact on the performance of firms, especially in developing countries like Nigeria. On the one hand, financial inclusion is measured using a multidimensional measure, which includes (i) firms having between 20-40 percent of their working capital financed through borrowing from the bank; (ii) firms having an overdraft facility to finance their operation and (iii) firms having a line of credit or loan from a financial institution. On the other hand, firm performance is measured using the lag total annual sales value of the firm in local currency unit. From the matching estimation, we find that whereas firms perform better with the aid of access to bank services, the extent differs in relation to the type of access they have. We interpret these results as showing that financial deepening increases firms' performance only dependent on the type of financial inclusion that is being observed.
Keywords: D60; E25; G20; I30; O55; 330; Financial inclusion; Manufacturing Firms; Development Nigeria